A polytetrafluoroethylene composite membrane with self-cleaning ability and preparation method thereof

By setting a fiber composite layer on the surface of the polytetrafluoroethylene composite film to form a fluorinated layer, the problem of the film being easily contaminated and difficult to clean is solved, and better mechanical properties and self-cleaning ability are achieved.

CN118876539BActive Publication Date: 2025-03-25QINGDAO ZHONGHAI ENVIRONMENTAL ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410893447.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-03-25
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The polytetrafluoroethylene composite film is easily contaminated when dealing with organic waste and is inconvenient for cleaning, which affects the aesthetics and use effect of the coating.

Method used

A polytetrafluoroethylene composite film consisting of an outer layer, an ePTFE layer and an inner layer are both fiber composite layers. The fluorinated layer is formed by coating and heat treatment of silicone coating and modified polyphenylene sulfide to improve the mechanical properties and soil resistance of the film.

Benefits of technology

The self-cleaning ability of the polytetrafluoroethylene composite film is realized, its resistance to deformation and mechanical properties are improved, and its anti-pollution and humidity resistance is enhanced, making it convenient for cleaning and maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of polytetrafluoroethylene composite membranes, specifically a polytetrafluoroethylene composite membrane with self-cleaning ability and a preparation method thereof, wherein the structure from top to bottom is: an outer layer, an ePTFE layer (expanded polytetrafluoroethylene layer) and an inner layer; the outer layer and the inner layer are both fiber composite layers; the fiber composite layer is obtained by sequentially applying a silicone coating and a modified polyphenylene sulfide suspension to a fiber cloth and heat treating the fiber cloth. The present invention forms a polytetrafluoroethylene composite membrane by respectively arranging fiber composite layers on the upper and lower surfaces of the ePTFE layer and compounding them, thereby improving the resistance of the ePTFE layer to deformation, thereby making the prepared polytetrafluoroethylene composite membrane have more excellent mechanical properties. And by setting the fiber composite layer process and the components used, the anti-pollution ability is improved, and the self-cleaning and easy-to-clean effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polytetrafluoroethylene composite membranes, in particular to a polytetrafluoroethylene composite membrane with self-cleaning ability and a preparation method thereof. Background Art

[0002] Organic waste includes urban sludge, livestock manure from aquaculture, straw waste from planting, etc. With the development of society, the problem of organic waste treatment has become increasingly prominent. Conventional organic waste treatment adopts landfill, concentration, conditioning, drying, incineration and other reduction, stabilization and harmless disposal processes. Membrane-covered aerobic fermentation is a new technology developed in recent years. It can increase the temperature of the pile, kill pathogens, eggs, seeds, etc., and improve the safety of organic waste treatment. The film used in membrane-covered aerobic fermentation is generally made of polytetrafluoroethylene, and the surface micropores of the commonly used membrane ePTFE membrane make it waterproof and breathable. However, the membrane body is easily contaminated by organic waste, but it is not easy to clean, which is not conducive to the appearance of the beautiful film. Therefore, we propose a polytetrafluoroethylene composite membrane with self-cleaning ability and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a polytetrafluoroethylene composite membrane with self-cleaning ability and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a polytetrafluoroethylene composite membrane with self-cleaning ability, the structure from top to bottom is: an outer layer, an ePTFE layer (expanded polytetrafluoroethylene layer) and an inner layer.

[0005] Furthermore, both the outer layer and the inner layer are fiber composite layers; the fiber composite layer is obtained by sequentially coating the fiber cloth with an organic silicon coating and a modified polyphenylene sulfide suspension and heat treating the fiber cloth.

[0006] Furthermore, the yarn material of the fiber cloth is polyester or polyamide, the yarn is selected from 210D to 900D, and the weight of the fiber cloth is 100 to 300g / m 2 .

[0007] Furthermore, the polytetrafluoroethylene composite membrane is obtained by laminating a fiber composite layer and an ePTFE layer.

[0008] Furthermore, the lamination is seam lamination, the interval between two adjacent seams is 0.5 to 0.8 m, and the width of the seams is 8 to 20 cm.

[0009] Furthermore, the thickness of the ePTFE layer is 15 to 65 μm.

[0010] A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability comprises the following processes:

[0011] A fiber composite layer is respectively arranged on the upper surface and the lower surface of the ePTFE layer, and laminated to form an outer layer and an inner layer respectively, so as to obtain a polytetrafluoroethylene composite membrane.

[0012] In the above technical solution, fiber composite layers are respectively arranged on the upper and lower surfaces of the ePTFE layer and composited to form a polytetrafluoroethylene composite membrane, which can improve the deformation resistance of the ePTFE layer and make the prepared polytetrafluoroethylene composite membrane have better mechanical properties.

[0013] Furthermore, the fiber composite layer is prepared by the following process:

[0014] The hydroxy-terminated polydimethylsiloxane, siloxane and a catalyst are mixed to obtain an organosilicon coating;

[0015] The organic silicon coating, modified polyphenylene sulfide, polytetrafluoroethylene and filler are mixed in ethanol and ultrasonically dispersed for 25 to 30 minutes to obtain a suspension;

[0016] The suspension is coated on the surface of the fiber layer, and heat treated to form a fluorinated layer to obtain a fiber composite layer.

[0017] Further, in the silicone coating, the mass ratio of terminal hydroxyl polydimethylsiloxane to siloxane is 100:(5-10);

[0018] The catalyst is dioctyltin dilaurate, and the amount used is 1.5% to 2.0% of the total mass of terminal hydroxyl polydimethylsiloxane and siloxane;

[0019] The siloxanes are trifluorotriethoxysilane (CAS No. 358-60-1), trifluoropropane trimethoxysilane (CAS No. 429-60-7), nonafluorohexyl trimethoxysilane (CAS No. 85877-79-8), tridecafluorooctyl triethoxysilane (CAS No. 51851-37-7), heptadecafluorodecyl trimethoxysilane (CAS No. 83048-65-1), 3-aminopropyl trimethoxysilane (CAS No. 13822-56-5), N-phenyl-3-aminopropyl trimethoxysilane (CAS No. 3068-76-6), γ-aminoethylaminopropyl trimethoxysilane (CAS No. : 1760-24-3), N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine (CAS No.: 51895-58-0), 2-(2-trimethoxysilylphenyl)ethanethiol (CAS No.: 334662-78-1), 2-ethyl-6-trimethoxysilylthiophenol (CAS No.: 194300-32-8), 2,4-dimethyl-6-trimethoxysilylthiophenol (CAS No.: 194300-28-2), [disulfide bis (methylene-4,1-phenylene methylene)] bis [triethoxy-] silane (CAS No.: 89552-66-9) Two or more of the following:

[0020] Furthermore, the siloxane is a mixture of heptadecafluorodecyltrimethoxysilane and [disulfide bis(methylene-4,1-phenylenemethylene)]bis[triethoxy-]silane, with a mass ratio of 1:(0.8-2.4).

[0021] Further, the suspension includes the following mass components: 60-180 g / L of silicone coating, 100-300 g / L of modified polyphenylene sulfide, 12-36 g / L of polytetrafluoroethylene and 12-36 g / L of filler;

[0022] PTFE is added in the form of an emulsion with a solid content of 60%.

[0023] Furthermore, the coating thickness of the suspension is 30-50 μm; the process conditions of the heat treatment are: temperature 220-240° C., and time 160-200 min.

[0024] Further, the modified polyphenylene sulfide is prepared by the following process:

[0025] The carboxylated polyphenylene sulfide is dispersed in N-methylpyrrolidone, a dispersant and a modifier are added, and the mixture is placed at a temperature of 180 to 240° C. and kept for reaction for 100 to 150 minutes; the mixture is washed, filtered, and vacuum dried to obtain the modified polyphenylene sulfide.

[0026] Further, the dispersant is polyethylene glycol;

[0027] The modifier is one or a mixture of γ-aminoethylaminopropyltrimethoxysilane and N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine;

[0028] The ratio of carboxylated polyphenylene sulfide and N-methylpyrrolidone is (10-30) g:100 mL;

[0029] The mass ratio of carboxylated polyphenylene sulfide, dispersant and modifier is 100:(3.0-3.3):(22-28).

[0030] Further, carboxylated polyphenylene sulfide is prepared by the following process:

[0031] Sodium sulfide and N-methylpyrrolidone are mixed, heated to 160-170°C, sodium hydroxide, p-dichlorobenzene and p-dichlorobenzoic acid are added, nitrogen is introduced, and the temperature is raised to 215-225°C under vacuum and high pressure, and the temperature is kept for 160-200 minutes; the temperature is raised to 265-275°C, and the reaction is carried out for 100-150 minutes; dilute hydrochloric acid is added for acidification, deionized water and ethanol are added for vigorous stirring, the mixture is allowed to stand for stratification, the supernatant is removed, and washing is repeated for 3-5 times. When the supernatant has no obvious sedimentation, the mixture is centrifuged and vacuum dried to obtain carboxylated polyphenylene sulfide.

[0032] Further, the ratio of sodium sulfide and N-methylpyrrolidone is (29-32) g:100 mL;

[0033] The carboxylated polyphenylene sulfide is prepared from the following components: by mass, 100 parts of p-dichlorobenzene, 9.0-9.5 parts of p-dichlorobenzoic acid, 2.4-2.7 parts of sodium hydroxide, and 133-138 parts of sodium sulfide.

[0034] Further, the filler is a mixture of one or more of silicon dioxide, titanium dioxide, and diatomaceous earth;

[0035] The filler is modified by the following process:

[0036] The filler and the coupling agent are mixed in ethanol, and ultrasonically treated for 160 to 200 minutes; centrifuged at a speed of 5500 to 6500 rpm, washed, and dried to obtain a modified filler.

[0037] Further, the ratio of filler, coupling agent, and ethanol (90v%) is 10g:(1.5-3.0)g:100mL;

[0038] The coupling agent is one of 2-(2-trimethoxysilylphenyl)ethanethiol, 2-ethyl-6-trimethoxysilylthiophenol, and 2,4-dimethyl-6-trimethoxysilylthiophenol.

[0039] In the above technical scheme, the fiber composite layer is obtained by coating the fiber cloth with a suspension and curing it by heat treatment. The suspension contains components of silicone coating, modified polyphenylene sulfide, polytetrafluoroethylene and filler. Among them, the modified polyphenylene sulfide is obtained by reacting carboxylated polyphenylene sulfide and aminosiloxane, and amidation, and can participate in the polycondensation reaction in the silicone coating component, increase the molecular crosslinking density of the fluorinated layer made by the suspension, bond the fibers in the fiber cloth, and further improve the mechanical strength of the fiber composite layer and the polytetrafluoroethylene composite layer made by it. The polyphenylene sulfide molecular chain segments are introduced into the fluorinated layer structure to make it have better heat resistance, mechanical strength and lower surface energy. At the heat treatment curing temperature, the polyphenylene sulfide segments can be cross-linked, so that the heat resistance, strength and bonding force between the fluorinated layer and the fiber cloth are improved, thereby improving the mechanical strength, water repellency and heat resistance of the fiber composite layer.

[0040] The silicone coating includes hydroxyl-terminated polydimethylsiloxane and siloxane used as a crosslinking agent. During the heat treatment curing stage, the hydroxyl groups in the hydroxyl-terminated polydimethylsiloxane and the silicon-oxygen bonds in the siloxane undergo polycondensation under the action of a catalyst, and the prepared silicone polymer can undergo physical crosslinking with polytetrafluoroethylene at high temperatures. The siloxanes selected are heptadecafluorodecyltrimethoxysilane and [disulfide bis(methylene-4,1-phenylenemethylene)]bis[triethoxy-]silane. Heptadecafluorodecyltrimethoxysilane introduces fluorine atoms into the composite layer, reduces the surface energy, and makes it have good water repellency, thereby improving the resistance of the polytetrafluoroethylene composite layer to dirt, achieving its self-cleaning and easy-to-clean effect; improving its anti-pollution ability, and it can be cleaned by washing with rainwater. [disulfide bis(methylene-4,1-phenylenemethylene)]bis[triethoxy-]silane increases the crosslinking degree of silicone curing and can participate in the crosslinking of polyphenylene sulfide, thereby further improving the mechanical properties of the fiber composite layer. In addition, silicone has excellent UV resistance, high temperature resistance and hydrophobicity, which makes the fluorinated layer have good weather resistance; and the flexibility of its molecular chain also helps to improve the high rigidity of the polyphenylene sulfide molecular chain. The resulting polytetrafluoroethylene composite layer can have more excellent mechanical strength, moisture and heat resistance, UV resistance and other comprehensive properties.

[0041] The suspension component also contains polytetrafluoroethylene. An appropriate amount of polytetrafluoroethylene can reduce the surface energy of the fluorinated layer and improve its high temperature resistance. If excessive addition is added, it will affect the bonding ability between the fluorinated layer and the fiber cloth and the wear resistance and mechanical strength of the fiber composite layer.

[0042] The filler is modified by coupling, and the coupling agent is a siloxane containing a mercapto group, which can cross-link with the broken disulfide bonds in the silicone during the heat treatment stage, participate in the curing of the system, and improve the mechanical properties, UV resistance and other comprehensive capabilities of the fluorinated layer.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. A self-cleaning polytetrafluoroethylene composite membrane and a preparation method thereof of the present invention can improve the resistance of the ePTFE layer to deformation by providing fiber composite layers on the upper and lower surfaces of the ePTFE layer, and thereby making the prepared polytetrafluoroethylene composite membrane have more excellent mechanical properties.

[0045] 2. The present invention discloses a polytetrafluoroethylene composite membrane with self-cleaning ability and a preparation method thereof, which is obtained by coating a fiber cloth with a suspension containing an organic silicone coating and modified polyphenylene sulfide and heat treating the fiber cloth. The organic silicone coating components include terminal hydroxyl polydimethylsiloxane and siloxane. The modified polyphenylene sulfide is obtained by reacting carboxylated polyphenylene sulfide and aminosiloxane, which can improve the mechanical properties of the fiber composite layer and its UV resistance, moisture and heat resistance, anti-fouling and self-cleaning abilities. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In the following specific implementations,

[0048] Fiber cloth: Oxford cloth, yarn count 420D×420D, weight 300g / m 2 , from Anhui Liqiang Textile Technology Co., Ltd.;

[0049] ePTFE layer: FL-CMFL0340, thickness 35-40 μm, from Beijing Fuliou Material Technology Co., Ltd.

[0050] Silicon dioxide: NO-O-001-2, from Shanghai Naio Nano Technology Co., Ltd.;

[0051] Polyethylene glycol: PEF400, from Merck Life Science;

[0052] Polytetrafluoroethylene emulsion: 4DC-S, solid content 60%, from Hangzhou Jingfu Technology Co., Ltd.;

[0053] Hydroxyl-terminated polydimethylsiloxane: molecular weight 2000, sourced from Chengdu Ounruis Reagent Co., Ltd.

[0054] The lamination process conditions are: temperature 140°C, duration 10s; hot melt adhesive: HT-8810, from Wenzhou Walter Hot Melt Adhesive Co., Ltd., adhesive amount 15g / m 2 ;

[0055] Sodium sulfide and N-methylpyrrolidone were dehydrated before use.

[0056] Embodiment 1: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0057] Step 1, preparation of modified polyphenylene sulfide:

[0058] 133 g of sodium sulfide and 420 mL of N-methylpyrrolidone were mixed, heated to 160° C., 2.4 g of sodium hydroxide, 100 g of p-dichlorobenzene and 9.0 g of p-dichlorobenzoic acid were added, nitrogen was introduced, and the temperature was raised to 215° C. under vacuum and high pressure, and the temperature was kept for 160 min; the temperature was raised to 265° C. and the reaction was carried out for 100 min; dilute hydrochloric acid was added for acidification, deionized water and ethanol were added and stirred vigorously, the mixture was allowed to stand for stratification, the supernatant was removed, and the mixture was washed repeatedly for 3 times. When the supernatant had no obvious sedimentation, the mixture was centrifuged and vacuum dried to obtain carboxylated polyphenylene sulfide;

[0059] Disperse 20g of carboxylated polyphenylene sulfide in 100mL of N-methylpyrrolidone, add dispersant polyethylene glycol and modifier γ-aminoethylaminopropyltrimethoxysilane, place at 180°C, and keep warm for 150min; wash, filter, and vacuum dry to obtain modified polyphenylene sulfide; the mass ratio of carboxylated polyphenylene sulfide, dispersant, and modifier is 100:3.0:22;

[0060] Step 2: Modification of filler:

[0061] 10 g of silica filler and 1.5 g of coupling agent 2-(2-trimethoxysilylphenyl)ethanethiol were mixed in 100 mL of 90% by volume ethanol, and ultrasonically treated for 160 min; centrifuged at 5500 rpm, washed, and dried to obtain a modified filler;

[0062] Step 3: Preparation of fiber composite layer:

[0063] The end-hydroxy polydimethylsiloxane, siloxane and 1.5% catalyst dioctyltin dilaurate are mixed to obtain an organic silicon coating; the mass ratio of the end-hydroxy polydimethylsiloxane and the siloxane is 100:5; the siloxane is a mixture of heptadecafluorodecyltrimethoxysilane and [disulfide bis (methylene-4,1-phenylene methylene)] bis [triethoxy-] silane, and the mass ratio is 1:0.8;

[0064] The organosilicon coating, modified polyphenylene sulfide, 60 wt% polytetrafluoroethylene emulsion and modified filler were mixed in ethanol and ultrasonically dispersed for 25 min to obtain a suspension;

[0065] The suspension is coated on the surface of the fiber layer with a coating thickness of 30 μm; the fiber layer is heat treated at 220° C. for 200 min to form a fluorinated layer, thereby obtaining a fiber composite layer; the suspension includes the following mass components: 60 g / L silicone coating, 100 g / L modified polyphenylene sulfide, 12 g / L polytetrafluoroethylene (20 g / L polytetrafluoroethylene emulsion) and 12 g / L modified filler;

[0066] Step 4: Preparation of polytetrafluoroethylene composite membrane:

[0067] A fiber composite layer is respectively arranged on the upper surface and the lower surface of the ePTFE layer, and laminated to form an outer layer and an inner layer respectively, to obtain a polytetrafluoroethylene composite membrane; the laminated composite is a seam composite, and two adjacent seams are arranged at an interval of 0.5m, and the width of the seam is 8cm.

[0068] Embodiment 2: A method for preparing a polytetrafluoroethylene composite membrane having self-cleaning ability, comprising the following process:

[0069] Step 1, preparation of modified polyphenylene sulfide:

[0070] 135g of sodium sulfide and 420mL of N-methylpyrrolidone were mixed, heated to 165°C, 2.5g of sodium hydroxide, 100g of p-dichlorobenzene and 9.2g of p-dichlorobenzoic acid were added, nitrogen was introduced, and the temperature was raised to 220°C under vacuum and high pressure, and the temperature was kept for 180min; the temperature was raised to 270°C, and the reaction was carried out for 120min; dilute hydrochloric acid was added for acidification, deionized water and ethanol were added and stirred vigorously, the mixture was allowed to stand for stratification, the supernatant was removed, and the mixture was washed repeatedly for 4 times, and the supernatant was centrifuged and vacuum dried until there was no obvious sedimentation, and carboxylated polyphenylene sulfide was obtained;

[0071] Disperse 20 g of carboxylated polyphenylene sulfide in 100 mL of N-methylpyrrolidone, add dispersant polyethylene glycol and modifier N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, place at 210°C, and keep warm for 120 minutes; wash, filter, and vacuum dry to obtain modified polyphenylene sulfide; the mass ratio of carboxylated polyphenylene sulfide, dispersant, and modifier is 100:3.2:25;

[0072] Step 2: Modification of filler:

[0073] 10 g of silica filler and 2.2 g of coupling agent 2-ethyl-6-trimethoxysilylthiophenol were mixed in 100 mL of 90% by volume ethanol, and ultrasonically treated for 180 min; centrifuged at 6000 rpm, washed, and dried to obtain a modified filler;

[0074] Step 3: Preparation of fiber composite layer:

[0075] The end-hydroxy polydimethylsiloxane, siloxane and 1.8% catalyst dioctyltin dilaurate are mixed to obtain an organic silicone coating; the mass ratio of the end-hydroxy polydimethylsiloxane and the siloxane is 100:8; the siloxane is a mixture of heptadecafluorodecyltrimethoxysilane and [disulfide bis (methylene-4,1-phenylene methylene)] bis [triethoxy-] silane, and the mass ratio is 1:16;

[0076] The organosilicon coating, modified polyphenylene sulfide, 60 wt% polytetrafluoroethylene emulsion and modified filler were mixed in ethanol and ultrasonically dispersed for 27 min to obtain a suspension;

[0077] The suspension is coated on the surface of the fiber layer with a coating thickness of 40 μm; the fiber layer is heat treated at 310° C. for 180 min to form a fluorinated layer, thereby obtaining a fiber composite layer; the suspension includes the following mass components: 120 g / L silicone coating, 200 g / L modified polyphenylene sulfide, 24 g / L polytetrafluoroethylene (40 g / L polytetrafluoroethylene emulsion) and 24 g / L modified filler;

[0078] Step 4: Preparation of polytetrafluoroethylene composite membrane:

[0079] A fiber composite layer is respectively arranged on the upper surface and the lower surface of the ePTFE layer, and laminated to form an outer layer and an inner layer respectively, to obtain a polytetrafluoroethylene composite membrane; the laminated composite is a seam composite, and the interval between two adjacent seams is 0.6m, and the width of the seam is 15cm.

[0080] Embodiment 3: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0081] Step 1, preparation of modified polyphenylene sulfide:

[0082] 138g of sodium sulfide and 420mL of N-methylpyrrolidone were mixed, heated to 170°C, 2.7g of sodium hydroxide, 100g of p-dichlorobenzene and 9.5g of p-dichlorobenzoic acid were added, nitrogen was introduced, and the temperature was raised to 225°C under vacuum and high pressure, and the temperature was kept for 200min; the temperature was raised to 275°C, and the reaction was carried out for 150min; dilute hydrochloric acid was added for acidification, deionized water and ethanol were added and stirred vigorously, and the mixture was allowed to stand for stratification, the supernatant was removed, and the mixture was washed repeatedly for 5 times. When the supernatant had no obvious sedimentation, the mixture was centrifuged and vacuum dried to obtain carboxylated polyphenylene sulfide;

[0083] Dispersing 20 g of carboxylated polyphenylene sulfide in 100 mL of N-methylpyrrolidone, adding dispersant polyethylene glycol and modifier N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, placing at 240°C, keeping the temperature for reaction for 100 min; washing, filtering, and vacuum drying to obtain modified polyphenylene sulfide; the mass ratio of carboxylated polyphenylene sulfide, dispersant, and modifier is 100:3.3:28;

[0084] Step 2: Modification of filler:

[0085] 10 g of silica filler and 3.0 g of coupling agent 2,4-dimethyl-6-trimethoxysilylthiophenol were mixed in 100 mL of 90% by volume ethanol, and ultrasonically treated for 200 min; centrifuged at 6500 rpm, washed, and dried to obtain a modified filler;

[0086] Step 3: Preparation of fiber composite layer:

[0087] The end-hydroxy polydimethylsiloxane, siloxane and 2.0% catalyst dioctyltin dilaurate are mixed to obtain an organic silicon coating; the mass ratio of the end-hydroxy polydimethylsiloxane and the siloxane is 100:10; the siloxane is a mixture of heptadecafluorodecyltrimethoxysilane and [disulfide bis (methylene-4,1-phenylene methylene)] bis [triethoxy-] silane, and the mass ratio is 1:2.4;

[0088] The organic silicon coating, modified polyphenylene sulfide, 60wt% polytetrafluoroethylene emulsion and modified filler are mixed in ethanol and ultrasonically dispersed for 30 minutes to obtain a suspension; the suspension is coated on the surface of the fiber layer with a coating thickness of 50μm; heat-treated at 320℃ for 160min to form a fluorinated layer to obtain a fiber composite layer; the suspension includes the following mass components: 180g / L organic silicon coating, 300g / L modified polyphenylene sulfide, 36g / L polytetrafluoroethylene (60g / L polytetrafluoroethylene emulsion) and 36g / L modified filler;

[0089] Step 4: Preparation of polytetrafluoroethylene composite membrane:

[0090] A fiber composite layer is respectively arranged on the upper surface and the lower surface of the ePTFE layer, and laminated to form an outer layer and an inner layer respectively, to obtain a polytetrafluoroethylene composite membrane; the laminated composite is a seam composite, and the interval between two adjacent seams is 0.8m, and the width of the seam is 20cm.

[0091] Comparative Example 1: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0092] Step 1: Preparation of fiber composite layer:

[0093] The end-hydroxy polydimethylsiloxane, tetraethyl orthosilicate and 1.5% dioctyltin dilaurate as a catalyst are mixed to obtain an organosilicon coating; the mass ratio of the end-hydroxy polydimethylsiloxane to the tetraethyl orthosilicate is 100:5;

[0094] The organosilicon coating, carboxylated polyphenylene sulfide, 60 wt% polytetrafluoroethylene emulsion and modified filler were mixed in ethanol and ultrasonically dispersed for 25 min to obtain a suspension;

[0095] The suspension is coated on the surface of the fiber layer with a coating thickness of 30 μm; the fiber layer is heat treated at 220° C. for 200 min to form a fluorinated layer, thereby obtaining a fiber composite layer; the suspension includes the following mass components: 60 g / L silicone coating, 100 g / L carboxylated polyphenylene sulfide, 12 g / L polytetrafluoroethylene (20 g / L polytetrafluoroethylene emulsion) and 12 g / L modified filler;

[0096] Step 2: modification of the filler and step 3: preparation of the polytetrafluoroethylene composite membrane are respectively the same as step 2 and step 4 in Example 1 to obtain a polytetrafluoroethylene composite membrane.

[0097] Comparative Example 2: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0098] Step 1: Preparation of fiber composite layer:

[0099] The end-hydroxy polydimethylsiloxane, tetraethyl orthosilicate and 1.5% catalyst dioctyltin dilaurate were mixed to obtain an organosilicon coating, which was applied to the surface of the fiber cloth with a coating thickness of 15 μm; the coating was cured and dried at 150° C. for 48 hours to form an organosilicon layer, and a fiber composite layer was obtained; the mass ratio of the end-hydroxy polydimethylsiloxane to the tetraethyl orthosilicate was 100:5;

[0100] The organosilicon coating, 60 wt% polytetrafluoroethylene emulsion and modified filler were mixed in ethanol and ultrasonically dispersed for 25 min to obtain a suspension;

[0101] The suspension is coated on the surface of the fiber layer with a coating thickness of 30 μm; the fiber layer is heat treated at 220° C. for 200 min to form a fluorinated layer, thereby obtaining a fiber composite layer; the suspension includes the following mass components: 60 g / L silicone coating, 12 g / L polytetrafluoroethylene (20 g / L polytetrafluoroethylene emulsion) and 12 g / L modified filler;

[0102] Step 2 The preparation of the polytetrafluoroethylene composite membrane is the same as step 4 in Example 1 to obtain a polytetrafluoroethylene composite membrane.

[0103] Comparative Example 3: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0104] Step 1: Preparation of fiber composite layer:

[0105] Carboxylated polyphenylene sulfide, 60wt% polytetrafluoroethylene emulsion and modified filler are mixed in ethanol, ultrasonically dispersed for 25 minutes to obtain a suspension; coated on the surface of the fiber cloth with a coating thickness of 30μm; heat treated at 220℃ for 200min to form a fluorinated layer to obtain a fiber composite layer; the suspension includes the following mass components: 100g / L carboxylated polyphenylene sulfide, 12g / L polytetrafluoroethylene (20g / L polytetrafluoroethylene emulsion) and 12g / L modified filler;

[0106] Step 2: modification of the filler and step 3: preparation of the polytetrafluoroethylene composite membrane are respectively the same as step 2 and step 4 in Example 1 to obtain a polytetrafluoroethylene composite membrane.

[0107] Comparative Example 4: A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, comprising the following process:

[0108] A fiber composite layer (420D PU coated nylon oxford fabric, weight 300g / m2) is arranged on the upper and lower surfaces of the ePTFE layer. 2 , from Suzhou Xikeer Industrial Co., Ltd.), laminated to form an outer layer and an inner layer respectively, to obtain a polytetrafluoroethylene composite membrane; the laminated composite is a seam composite, with an interval of 0.5m between two adjacent seams, and a seam width of 8cm.

[0109] Experiment: Take the polytetrafluoroethylene composite membranes obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results:

[0110] Mechanical properties test: Use a tensile testing machine to test the tensile strength of the sample, with a tensile rate of 100mm / min;

[0111] Antifouling performance test: Use a contact angle tester to test the contact angle of the sample surface. The test droplet is deionized water with a droplet volume of 4μL. Test five areas of the sample and take the average value.

[0112] UV aging performance test: expose the sample to ultraviolet radiation for 7 days to test its mechanical properties; UV wavelength is 340nm, and the irradiation intensity is 50W / m 2 ;

[0113] Heat resistance test: Place the sample in a hot and humid environment for 48 hours and test its mechanical properties again; the experimental temperature is 100°C and the relative humidity is 95%.

[0114]

[0115] According to the data in the above table, we can clearly draw the following conclusions:

[0116] The polytetrafluoroethylene composite membranes obtained in Examples 1-3 are compared with the polytetrafluoroethylene composite membranes obtained in Comparative Examples 1-4. The test results show that:

[0117] Compared with the comparative example, the polytetrafluoroethylene composite membranes obtained in Examples 1-3 have higher breaking strength and contact angle data, and better retention of breaking strength after UV aging and wet heat aging. This fully demonstrates that the present invention achieves improvement of the mechanical strength, wet heat resistance, UV resistance and antifouling ability of the polytetrafluoroethylene composite membrane.

[0118] Compared with Example 1, the fiber composite layer in Comparative Example 1, the silicone coating is made of terminal hydroxyl polydimethylsiloxane and tetraethyl orthosilicate, and the suspension components are silicone coating, carboxylated polyphenylene sulfide, polytetrafluoroethylene and modified filler. The fiber composite layer in Comparative Example 2, the silicone coating is made of terminal hydroxyl polydimethylsiloxane and tetraethyl orthosilicate, and the suspension components are silicone coating, polytetrafluoroethylene and modified filler. The fiber composite layer in Comparative Example 3 is formed by coating a suspension made of carboxylated polyphenylene sulfide, polytetrafluoroethylene and modified filler on a fiber cloth and curing. The fiber composite layer in Comparative Example 4 is a commercially available product. The polytetrafluoroethylene composite membranes obtained in Comparative Examples 1-4 have decreased breaking strength and contact angle data, and the retention of breaking strength after UV aging and wet heat aging is also decreased. It can be seen that the preparation process of the polytetrafluoroethylene composite membrane and the arrangement of the components used in the present invention can promote the improvement of the mechanical strength, moisture and heat resistance, UV resistance and anti-fouling ability of the polytetrafluoroethylene composite membrane.

[0119] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0120] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability, characterized in that: The structure from top to bottom is: outer layer, ePTFE layer and inner layer; The outer layer and the inner layer are both fiber composite layers; the fiber composite layer is made by the following process: The hydroxy-terminated polydimethylsiloxane, siloxane and a catalyst are mixed to obtain an organosilicon coating; The organic silicon coating, modified polyphenylene sulfide, polytetrafluoroethylene and filler are mixed in ethanol and ultrasonically dispersed for 25 to 30 minutes to obtain a suspension; The suspension is applied to the surface of the fiber layer, and heat-treated to form a fluorinated layer, thereby obtaining a fiber composite layer; The mass ratio of the terminal hydroxyl polydimethylsiloxane to siloxane is 100:(5-10); The catalyst is dioctyltin dilaurate, and the amount used is 1.5% to 2.0% of the total mass of terminal hydroxyl polydimethylsiloxane and siloxane; The siloxane is a mixture of heptadecafluorodecyltrimethoxysilane and [disulfide bis(methylene-4,1-phenylenemethylene)]bis[triethoxy-]silane, with a mass ratio of 1:(0.8-2.4); The modified polyphenylene sulfide is prepared by the following process: Dispersing carboxylated polyphenylene sulfide in N-methylpyrrolidone, adding a dispersant and a modifier, placing at 180-240° C., and keeping the temperature for 100-150 minutes; washing, filtering, and vacuum drying to obtain modified polyphenylene sulfide; The dispersant is polyethylene glycol; the modifier is one of γ-aminoethylaminopropyltrimethoxysilane and N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine; The mass ratio of carboxylated polyphenylene sulfide, dispersant and modifier is 100:(3.0-3.3):(22-28).

2. The method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability according to claim 1, characterized in that: The yarn material of the fiber cloth is polyester or polyamide, the yarn selection is 210D~900D, and the gram weight of the fiber cloth is 100~300g / m 2 .

3. The method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability according to claim 1, characterized in that: The polytetrafluoroethylene composite membrane is obtained by laminating a fiber composite layer and an ePTFE layer.

4. A method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability according to any one of claims 1 to 3, characterized in that: Including the following processes: A fiber composite layer is respectively arranged on the upper surface and the lower surface of the ePTFE layer, and laminated to form an outer layer and an inner layer respectively, so as to obtain a polytetrafluoroethylene composite membrane.

5. The method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability according to claim 1, characterized in that: The suspension comprises the following mass components: 60-180 g / L of organosilicon coating, 100-300 g / L of modified polyphenylene sulfide, 12-36 g / L of polytetrafluoroethylene and 12-36 g / L of filler; The coating thickness of the suspension is 30-50 μm; the process conditions of the heat treatment are: temperature 220-240° C., and time 160-200 min.

6. The method for preparing a polytetrafluoroethylene composite membrane with self-cleaning ability according to claim 1, characterized in that: The filler is a mixture of one or more of silicon dioxide, titanium dioxide and diatomaceous earth; the filler is modified, and the modification process is: the filler and the coupling agent are mixed in ethanol, and ultrasonic treatment is performed for 160 to 200 minutes; centrifugation is performed at a speed of 5500 to 6500 rpm, washing, and drying to obtain the modified filler; The ratio of filler, coupling agent and ethanol is 10g:(1.5-3.0)g:100mL; The coupling agent is one of 2-(2-trimethoxysilylphenyl)ethanethiol, 2-ethyl-6-trimethoxysilylthiophenol, and 2,4-dimethyl-6-trimethoxysilylthiophenol.

Citation Information

Patent Citations

  • Preparation method of expanded polytetrafluoroethylene composite thermal insulation film

    CN117162638A